Adult late-onset limb-girdle muscular dystrophy R1/2A complicated by parathyroid adenoma and sick sinus syndrome: a case report and literature review - Xuelian Hong; Fengfeng Jiang; Liuqing Wang (BMC Musculoskeletal Disorders)
Abstract Background Limb-girdle muscular dystrophy (LGMD) is a group of hereditary myopathies. This group of diseases is highly heterogeneous in terms of genetic mode, age at onset, and disease progression; therefore, they are easily misdiagnosed and missed in clinical practice. Case presentation We describe a case of adult late-onset LGMD R1/2A in a 56-year-old female patient. The patient experienced elevated creatine kinase levels lasting 5 years, muscle soreness of the limbs lasting 4 years, and exacerbation of limb fatigue lasting 1 month. Early in the course of the disease, the patient experienced severe bradycardia and was later diagnosed with sick sinus syndrome. In addition to cardiac involvement, our patient also had primary hyperparathyroidism during the disease course, which was confirmed pathologically as a parathyroid adenoma. A biopsy of the left biceps showed pathological manifestations of mild myogenic damage. All-exon gene sequencing confirmed the diagnosis of LGMD R1/2A, and she was treated with vitamin E, vitamin B2, and coenzyme Q. Due to atrial fibrillation secondary to sick sinus syndrome, a pacemaker was implanted. Conclusion The patient in this case study had adult late-onset LGMD R1/2A with cardiac involvement and functional parathyroid adenoma, which is rare and clinically significant. Therefore, early clinical identification, diagnosis, as well as targeted and active treatments can improve the prognosis of such patients.